Prevalence of prediabetes and associated factors among community members in Rural Isingiro district - Ampeire, Isaac Petit; Kawugezi, Peter Chris; Mulogo, Edgar Mugema (Research square, 2022)
Background: In rural Uganda many people are either pre-diabetic or diabetic, however they do not know that these conditions afflict them. The burden of pre-diabetes in rural Isingiro had not previously been determined. The study examined the prevalence of pre-diabetes and associated factors. Methods: A cross-sectional survey that enrolled 370 participants aged between 18 and 70 years was conducted in the Kabuyanda sub-county, rural Isingiro district in March 2021. Multistage sampling and systematic random sampling was conducted to select eligible households and data was collected using a pretested WHO STEP-wise protocol questionnaire. The primary outcome was Prediabetes (FBG=6.1mmol/l to 6.9mmol/l), calculated as a proportion. Chi-square tests and multivariate logistic regression models were performed for data analysis using STATA. Results: The prevalence of Prediabetes was 9.19% (95% CI 6.23-12.14). Factors independently associated with pre-diabetes were; advancing age [AOR=5.771 95% CI=1.031-32.306, P=0.046], moderate-intensity work [AOR=2.637 95%CI=1.233-5.636, P=0.012], high level of consumption of diet categorized as protective [AOR=5.657 95%CI=1.679-19.054, P=0.005] and body mass index [AOR=3.608 95% CI=1.414- 9.206, P=0.007] were significantly associated with Prediabetes. Conclusion: Prediabetes is prevalent among adult community members in rural Isingiro, southwestern Uganda. Age and lifestyle factors predict Prediabetes in this rural population, suggesting a need for targeted health promotion interventions.
Keywords: Uganda; Prediabetes; Community members